Inhibition of cultured cell growth by vascular endothelial cadherin (cadherin-5/VE-cadherin). - Caveda, L (1996)
Endothelial cell proliferation is inhibited by the establishment of cell to cell contacts. Adhesive molecules at junctions could therefore play a role in transferring negative growth signals. The transmembrane protein VE-cadherin (vascular endothelial cadherin/cadherin-S) is selectively expressed at intercellular clefts in the endothelium. The intracellular domain interacts with cytoplasmic proteins called catenins that transmit the adhesion signal and contribute to the anchorage of the protein to the actin cytoskeleton. Transfection of VE-cadherin in both Chinese hamster ovary (CHO) and L929 cells confers inhibition of cell growth. Truncation of VE-cadherin cytoplasmic region, responsible for linking catenins, does not affect VE-cadherin adhesive properties but abolishes its effect on cell growth. Seeding human umbilical vein endothelial cells or VE-cadherin transfectants on a recombinant VE-cadherin amino-terminal fragment inhibited their proliferation. These data show that VE-cadherin homotypic engagement at junctions participates in density dependent inhibition of cell growth. This effect requires both the extracellular adhesive domain and the intracellular catenin binding region of the molecule.